Safety, Tolerability and Pharmacokinetics of Single Ascending and Multiple Oral Doses of Tegoprazan in Healthy Chinese Subjects - He, Jinjie; Cao, Guoying; Yu, Jicheng; Wang, Jingjing; Cheng, Nengneng; Wu, Jufang; Zhang, Jing; Wu, Xiaojie; Zhang, Basheng; Lu, Jiayan; Chen, Shangzhi (Clinical drug investigation, 2021)
Background and Objectives Tegoprazan is one of the potassium-competitive acid blockers (P-CABs). It exhibits its anti-secretory effects by competitively and reversibly blocking the availability of K + of the H + , K + -ATPase. This study was designed to investigate the safety and pharmacokinetics of tegoprazan in healthy Chinese subjects. Methods Thirty-eight healthy Chinese subjects were recruited in this randomized, single-center, double-blind, placebo-controlled study, with a single ascending dose of 50, 100, 200 mg and a multiple dose of 100 mg for 10 days. The plasma concentration of tegoprazan was determined by a validated liquid chromatography tandem mass spectrometry (LC–MS/MS) method. Pharmacokinetics were evaluated via non-compartmental and compartmental model analysis. Safety was assessed by physical examinations, vital signs, clinical laboratory tests, and electrocardiograms. Results No serious adverse event was observed in this study. After single-dose administration (50, 100 and 200 mg), tegoprazan was rapidly absorbed with a median maximum measure plasma concentration ( T max ) at 0.5 h and declined with a terminal (elimination) half-life ( t 1/2 ) of 3.87–4.57 h. The maximum measured plasma concentration ( C max ) for tegoprazan was 813.80, 1494.60 and 2829.00 ng/mL. Meanwhile, the corresponding area under the concentration–time curve (AUC) from time zero to infinity (AUC 0−inf ) was 2761.00, 5980.05 and 11,044.72 ng∙h/mL in 50, 100, 200 mg group, respectively. Dose-dependent increase was observed in the value of C max and AUC after administration of tegoprazan 50 to 200 mg. The two-compartment model well described the pharmacokinetic profile of tegoprazan. In the steady state, no accumulation was found after repeated administration at the 100-mg dose level. No experimental differences were found based on gender. Conclusions Tegoprazan was well tolerated in the dose range of 50–200 mg in single- and 100 mg in multiple-dose studies. Tegoprazan shows dose linearity with oral administration after a single dose of 50 to 200 mg and less drug accumulation after 10 days of continuous administration in 100 mg.